Ionic Liquid-Based Dispersive Liquid-Liquid Microextraction Combined with Flame Atomic Absorption Spectrometry for Determination of Silver in Water Samples - Dehghani Mohammad Abadi, M.; Chamsaz, M.; Arbab-Zavar, M.H. (Asian Journal of Chemistry, 2013)
A new, simple and highly sensitive dispersive liquid-liquid microextraction method using an ionic liquid, 1-butyl-3-methylimidazolium hexafluorophosphate ([C4MIM][PF6]), for silver determination at trace levels was developed by flame atomic absorption spectrometry in water samples. Diethyl dithiocarbamate (DDTC) was employed as a chelating agent to form Ag-DDTC complex for extracting silver ions from aqueous solution into the fine droplets of [C4MIM][PF6]. Some effective factors influencing the microextraction efficiency include the pH, the diethyl dithiocarbamate concentration, type and volume of disperser solvent, the amount of ionic liquid, the ionic strength and the centrifugation time were investigated and optimized. At the optimum experimental conditions, the limit of detection based on 3Sb was 3.0 μg L-1. The relative standard deviation for five replicate determinations of 200 μg L-1 Ag was 2.9 %. The calibration graph was linear in the range of 15-300 μg L-1 with a correlation coefficient of 0.9961. The applicability of the proposed method was evaluated by determination of trace amounts of silver in water samples.